Governing Teacher Resilience: A Structural Model of Resilience and Performance Among Primary School Teachers in Post-Pandemic Indonesia - Aji Fauziana Ridwan; Arie Rakhmat Riyadi; Juntika Nurihsan; Mubiar Agustin (Dealings Foundation Institute, 2026)
This research examines the extent to which resilience predicts the performance of primary school teachers in Indonesia, identifies the major dimensions of resilience, and proposes a structural model for teacher’s’ professional development. This study using quantitative methods and involved 775 primary school teachers from four provinces such as West Java, DKI Jakarta, Central Java, and North Sumatra were selected using stratified random sampling approach. The result of this research inidicated there are resilience significantly predicted teachers performance (β = 0.452, p < 0.001, f² = 1.099) with an R² of 0.524, explaining 52.4% of performance variance. EFA identified three major dimensions of resilience: personal competence (λ = 0.70), social resources (λ = 0.71), and structured style (λ = 0.68). The scores distribution indicated that the majority of teachers on the high range (M_resilience = 4.37; M_performance = 4.38). Interestingly, this is the first study to introduces Teacher Resilience and Performance Integration Model (TRPIM) in Southeast Asia, integrating personal, social, and structural factors within Indonesia’s post-pandemic educational context. Based on the research, researcher recommends concrete policy recommendations, such as incorporating resilience training into mandatory professional programs (PPG/PKB), establishing School Resilience Support Teams, and developing a National Teacher Resilience Index. The methodologically, the research addresses prior limitations by employing a multidimensional PLS-SEM approach with a large sample (N=775). In contrast to previous local research (R² = 0.31), this study provides significant theoretical insights alongside practical recommendations aimed at enhancing the overall quality of primary education in Indonesia.